2002
DOI: 10.1034/j.1600-0781.2002.180205.x
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study on phototoxicity and the photosensitization potential of ketoprofen, suprofen, tiaprofenic acid and benzophenone and the photocross‐reactivity in guinea pigs

Abstract: From the test results, it appears that benzoyl radical is the key structure for photosensitivity and the photocross-reactivity of ketoprofen, suprofen and tiaprofenic acid. The whole structure of benzophenone was needed to induce photosensitization of benzophenone. The animals that were photosensitized from the entire structure of benzophenone did not photocross-react to ketoprofen, suprofen or tiaprofenic acid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 22 publications
0
32
0
Order By: Relevance
“…Negative phototoxicity was observed in a guinea pig skin phototoxicity study of ketoprofen (Sugiura et al, 2002). Mice given ketoprofen by single oral dosing and irradiated with UV-A did not demonstrate any change due to the phototoxicity (Ljunggren and Lundberg, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…Negative phototoxicity was observed in a guinea pig skin phototoxicity study of ketoprofen (Sugiura et al, 2002). Mice given ketoprofen by single oral dosing and irradiated with UV-A did not demonstrate any change due to the phototoxicity (Ljunggren and Lundberg, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…1 In an experimental study, it was found that benzoyl radical is the key structure that provokes photosensitivity and the photo cross-reactivity of KP, suprofen and tiaprofenic acid. 2 As that radical is common in benzophenone ultraviolet (UV) filters, cross-reactions are familiar with sunscreens containing mainly oxybenzone.…”
Section: Ketoprofen ([Rs]2-[3-benzoylphenyl]-propionic Acid) (Kp) Is mentioning
confidence: 99%
“…Although the free radical species were speculated to be benzophenone, [9][10][11][12] benzoyl radical, 13) carbonyl radical 14) and superoxide anion, 15) their true identities remain unknown to this day. We elucidated the pathways for the photo-degradation of ketoprofen and the generation of free radicals in our previous study.…”
mentioning
confidence: 99%